Stigma and coping experiences in Latinx individuals at clinical high‐risk for psychosis. Issue 1 (4th February 2021) - Ruiz, Bernalyn; Ceccolini, Christopher J.; Shah, Binoy B.; Crump, Francesca; Girgis, Ragy R.; Brucato, Gary; Yang, Lawrence H.; Corcoran, Cheryl M.
Abstract: Aim: The experiences of culturally diverse individuals at clinical high‐risk for psychosis (CHR) is not well studied. Exploratory research needs to examine whether differences exist between racial/ethnic groups within the CHR population. Understanding experiences of Latinx patients is of importance, as the Latinx population represents the most rapidly growing paediatric population in the United States and they face significant barriers to mental health treatment. Because Latinx persons experience high rates of mental illness‐based stigma and discrimination in their communities, they may face additional stigma‐based barriers to CHR treatment. Method: Twenty‐six participants (15 Latinx, 11 non‐Latinx white/NLW) who met CHR criteria based on the Structured Interview for Psychosis‐Risk Syndromes (SIPS) were interviewed regarding stigma associated with CHR identification and symptoms. Using a consensus‐based open‐coding thematic analysis approach, data were analysed for stigma, discrimination, and coping responses. Results: Instances of internalization of stereotypes appeared to be more salient to NLW participants than Latinx participants, and Latinx participants reported seemingly more anticipated rejection from stereotypes than NLW participants. Experiences of discrimination also appeared to be more salient to Latinx participants than NLW participants. Moreover, Latinx participants reported evidently greater instances of discrimination across anticipated, individual, and structural discrimination . Finally, while covering strategies appeared to be more salient to NLW's, Latinx clients more often described using secrecy as well as a greater range of coping responses, including empowerment . Conclusion: While the experience of anticipated rejection appeared to be more salient to Latinx CHR participants and they seemingly report more secrecy than NLW, they also engaged in empowerment‐ related coping strategies. Future research should continue to explore the roles of cultural values in influencing coping strategies among CHR individuals.